A novel mouse Fgfr2 mutant, hobbyhorse (hob), exhibits complete XY gonadal sex reversal. - Pam Siggers; Gwenn-Aël Carré; Debora Bogani; Nick Warr; Sara Wells; Helen Hilton; Chris Esapa; Mohammad K Hajihosseini; Andy Greenfield (PLoS ONE)
The secreted molecule fibroblast growth factor 9 (FGF9) plays a critical role in testis determination in the mouse. In embryonic gonadal somatic cells it is required for maintenance of SOX9 expression, a key determinant of Sertoli cell fate. Conditional gene targeting studies have identified FGFR2 as the main gonadal receptor for FGF9 during sex determination. However, such studies can be complicated by inefficient and variable deletion of floxed alleles, depending on the choice of Cre deleter strain. Here, we report a novel, constitutive allele of Fgfr2, hobbyhorse (hob), which was identified in an ENU-based forward genetic screen for novel testis-determining loci. Fgr2hob is caused by a C to T mutation in the invariant exon 7, resulting in a polypeptide with a mis-sense mutation at position 263 (Pro263Ser) in the third extracellular immunoglobulin-like domain of FGFR2. Mutant homozygous embryos show severe limb and lung defects and, when on the sensitised C57BL/6J (B6) genetic background, undergo complete XY gonadal sex reversal associated with failure to maintain expression of Sox9. Genetic crosses employing a null mutant of Fgfr2 suggest that Fgr2hob is a hypomorphic allele, affecting both the FGFR2b and FGFR2c splice isoforms of the receptor. We exploited the consistent phenotype of this constitutive mutant by analysing MAPK signalling at the sex-determining stage of gonad development, but no significant abnormalities in mutant embryos were detected.